Testing featural and holistic composite technologies under different methods of face recall - Prag, Bhavesh (Department of Psychology, 2014)
This thesis evaluates the effectiveness of two facial composite systems, used to produce facial images of alleged perpretators of crime, under varying conditions in two experiments. The first system is called E-face, a configural eigenfaced-based system originally developed at the University of Cape Town and currently undergoing further revisions; the second is called Faces, a featural system currently being used by several law enforcement agencies around the world.